ELECTORAL OFFENSES AS WHITE-COLLAR CRIME: A CASE STUDY - Kusno; Sumaryanto, Dr. Djoko (jfpublisher, 2023)
Indonesia is a democratic country whose leaders are elected by society. Unfortunately, there are still some criminal offenses in its implementation. Therefore, this research aims to find out the criminal sanctions applied in the Law against criminal offenses in general elections. The inventory data collection is implemented through empirical research methods through jurisprudence research in the form of court decisions on election offenses and library research. There are two sources in this research, these are (1) primary sources (court decisions on election offenses in accordance with Law No. 7/2017 on general elections); (2) secondary sources (legal journals, various scientific works, books, and documents relevant to the research topic). This research indicated that the criminal provisions in the ius constituendum in the Election Law are still not effective in providing a deterrent effect, as indicated by the high rate of criminal election offenses over the years. In addition, the facts indicated that court decisions on election crimes are generally decided with lenient criminal sanctions, smaller than the criminal provisions in the laws and regulations, which are less than 6 months. Meanwhile, the elements of the criminal offenses are suitable for aggravated sanctions because the perpetrators are organizers and officials. Unfortunately, the average judge considered the purpose of deterrent punishment which emphasizes awareness.